Natural variation in Brachiaria and existing germplasm collections - Keller-Grein, Gerhard; Maass, Brigitte L.; Hanson, Jean (International Center for Tropical Agriculture, 1996)
Seven perennial species of African origin - Brachiaria arrecta, B. brizantha, B. decumbens, B. dictyoneura, B. humidicola, B. mutica, and B. ruziziensis - have been used as fodder plants, particulary in tropical America. The history of the commercial cultivars is given, and their most important attributes are described. Access to germplasm diversity is essential for plant cultivar Development. The world's major ex situ collections of Brachiaria germplasm are listed, together with descriptions of their holdings and management. The biogeographic origin of major species and the natural variation in terms of morphology and isozymes are described. Needs for future collection and conservation are identified.